(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
This article explores the historical development of the education in Uzbekistan during Soviet Union period till our days. Additionally, it discusses the challenges on promoting the education in the country after the collapse of Soviet Union. Also it states the significant role of international organizations in reforming Uzbek model in education.